Public Opinion Toward Diverse Types of Police Reform Post-2020: The Impact of Perceptions, Experiences, and Racial Resentment - Mancini, Christina (Crime & delinquency, 2024)
Prior scholarship has tapped public preferences toward policing policy. Still, there is a need to continue to monitor public opinion given recent events. Post George Floyd, several reforms have been proposed: accountability and oversight initiatives (e.g., citizen boards, mandatory reviews), diversion of funds away from policing, and/or greater funding for police. Theory and research suggest that sentiments regarding these reforms are likely divided and vary based on perceptions of and experiences with police, as well as racial resentment. Drawing on a 2021 national poll, this study examined public support for several diverse reforms. Broad approval was evident for most reforms. However, support was contingent on perceptions of and experiences with the police, racial resentment, and socio-demographic factors. Implications are discussed.